Improved Teamwork and Implementation of Clinical Pathways in a Congenital Heart Surgery Program. Issue 1 (January 2019) - Willis, Tina Schade; Yip, Theodore; Brown, Karla; Buck, Scott; Mill, Michael
Abstract : Introduction: Complex surgical populations are at increased risk of morbidity, especially when experiencing variations in care and poor teamwork. The goal of this project was to improve teamwork and decrease variations in care in a pediatric congenital heart surgery population by implementing Integrated Clinical Pathways (ICPs) on a foundation of teamwork training. Methods: A core team used project management for completion of the project and measurement of success. The leadership team created a new operations infrastructure for the program to effectively implement and sustain improvement. Master trainers targeting teams caring for the patient population completed teamwork training and coaching. ICPs were designed and implemented using iterative tests of change with the assistance of an expert panel. Results: Three of the 4 units experienced a significant improvement in teamwork after training and coaching. The area without a significant change was one with high-level teamwork training already in place. ICPs were implemented in 2 patient subpopulations. We detected a decrease in total hours intubated using statistical process control charts in both of the ICP patient populations. Despite a decrease in intubation hours, we did not detect a reduction in length of stay in days. The infrastructure for the program was successfully implemented and remains in place 6 years later. Conclusions: Teamwork can be improved with an efficiently delivered training and coaching program. On a foundation of teamwork, ICPs can be implemented and sustained if a supporting infrastructure is in place including program leadership, buy-in from all teams, project management, and ongoing measurement. Abstract : Supplemental Digital Content is available in the text.